Personality Traits and Infidelity Propensity: A Systematic Review - Allahgoliyari, Malihe; Ajdarbin, Bahareh (Mental Health and Lifestyle Journal, 2024)
This study presents a systematic review of the relationship between personality traits and infidelity propensity. This review aimed to synthesize empirical findings to determine the relationships between major personality frameworks (Big Five traits, Dark Triad traits, attachment styles) and frameworks regarding infidelity-related attitudes, intentions, and behaviors. A systematic review was done by searching the three databases (Scopus, WOS, Google Scholar) for the papers published between the years (2016-2024). Upon considering the inclusion and exclusion criteria, the analyzed studies were limited to the empirical, peer-reviewed ones. The studies were then analyzed, utilizing a formal framework for structuring an analysis. Findings suggest inconsistency in personality traits and the Big Five model in association with infidelity-related outcomes. However, the personality trait of extraversion demonstrated mixed association of infidelity-related outcomes. In the Dark Triad, psychopathy and narcissism, consistently predicted infidelity behaviors and the breadth of personality dimensions. In contrast, Attachment styles showed inconsistency among studies suggesting the effects of a more context-dependent role. Additionally, results show that the risk of infidelity is related to factors such as relational, cultural, and contextual factors, such as degree of marital satisfaction, characteristics of the partner, and socioeconomic conditions. Finally, the review argues that infidelity is a phenomenon that needs an explanation beyond the personality of individuals. Thus, integrated models of infidelity that include dispositional and contextual factors are needed.